Pengujian Iritasi dan Sensitisasi Bahan Aktif Imidakloprid dalam Formulasi Insektisida - Syifa Nabilah Subakti Putri; Ichsan Nurul Bari; Gofarana Wilar; Abdurahman Ridho (UIN Sunan Gunung Djati Bandung, 2021)
Imidacloprid is a synthetic chemical compound used as an insecticide product. Despite the benefits that insecticides provided in controlling plant pests and increasing crop yields, the use of insecticides was associated with side effects in humans The purpose of this study was to evaluate the active ingredient of imidacloprid 200 g/l in an insecticide formulation to ensure the safety of the pesticide for the applicator. This study was conducted based on appropriate toxicological tests and assessment based on pre-clinical tests in the form of evaluation of irritation and sensitization. The method used was descriptive quantitative based on the OECD 404, 405, and 406 guidelines for albino New Zealand rabbits and adult Dunkin Hartley albino guinea pigs. The results showed that the imidacloprid compound did not cause irritation symptoms in the eyes (cornea, iris, conjunctiva, and chemosis) and skin (erythema and edema) with a score of zero (0). In addition, the results of the sensitization test at a concentration of 12.5 - 100% did not show the formation of erythema which was indicated by a score of zero (0). In conclusion, imidacloprid 200 g/l did not caused irritation and sensitivity reactions in test animals so this compound is safe to use as an insecticide.